Innovative micro physiological systems for vaccine development - Kendra Reynaud; Scott Atwell; Christophe Védrine; Cyril Guyard; Laurent Beloeil (Human Vaccines & Immunotherapeutics)
Micro Physiological systems (MPS) are biomimetic platforms that reconstitute the complex architecture of human organs and tissues in vitro. MPSs have the capacity to improve clinical development pipelines as they address certain translational limitations that exist in other pre-clinical models by providing human-relevant microenvironments. These platforms have already demonstrated their potential in vaccine development, as several variations of MPSs have recently been published that provided results relevant to vaccine trials in humans. Previous MPSs include approximations of peripheral and lymphoid tissue in static platforms to study the innate and adaptive response to vaccination, as well as a lymphoid-follicle-on-chip under dynamic flow which produces antigen-specific antibodies to vaccination. Up-and-coming devices could be used to study the interplay between vaccine reactogenicity and innate immune stimulation, and thereby derisk vaccine targets by elucidating their inflammatory profiles prior to advancement to clinical trials.